Vytápění funkcionalistické vily - Křikava, Michal (Vysoké učení technické v Brně. Fakulta stavební, 2015)
Diplomová práce řeší návrh vytápění funkcionalistické vily Stiassni. Objekt se nachází v Brně a byl využíván jako vládní vila. Předmětem práce je výběr vhodné varianty ze tří zdrojů tepla - automatický kotel na pelety, kotel na plyn a olejový kotel. Teoretická část je zaměřená na historii vily Stiassni, funkcionalismus a jiné památky funkcionalismu. Projektová část řeší návrh otopného systému se zvolenou variantou zdroje tepla, kterou je kotel na pelety.

This master´s thesis focuses on a design of a heating system in the functionalist villa Stiassni. The building is located in Brno and was used as a government villa. The objec-tive of this work is to select the appropriate type of heating system out of three differ-ent heat sources – an automatic pellet boiler, a gas boiler and an oil boiler. The theo-retical part is focused on the history of the villa Stiassnia, functionalism itself and other functionalist monuments. In the project part, the design of a heating system using the chosen type of heat source, which is a pellet boiler, is described.
Heating of the functionalist Villa
Keywords: vila; vytápění; litinová otopná tělesa; konvektory; pelety; kotel na pelety; plynové kotle; olejové kotle; příprava teplé vody; Villa; heating; cast iron radiators; convectors; pellets; pellet boiler; gas boiler; oil boiler; preparation of hot water